Syaikh Abdul Latief Syakur’s View on Moral Values in Tafsīr Surah Al-Mukminūn - Wahidi, Ridhoul; Shabir, Muslich; Junaidi, Akhmad Arif (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
Akhlak (morals) is a very important part in human life, without which men will not reach the degree of a noble man. On contrary, human beings having good akhlak can distinguish between good and bad deeds to become a noble man. The issue of morality is currently experiencing acute decadence that must be quickly overcome by various circles. One of the ways is through learning the thinking of earlier muslims scholars. One of the earlier Islamic scholars is Syaikh Abdul Latief Syakur, one of the local ulamas in Minangkabau, whose academic background had a direct contact with the dynamics of Middle Eastern scholarship,and who contributed a lot of thoughts to uplift the dignity of the nation through morals. As a scholar, Syaikh Abdul Latief Syakur presented and describedseveral moral values to overcome the present moral decadence through his thoughts set forth in his work Tafsīr Surah al-Mukminūn. The application of moral values in this tafsir work contributes to the present moment by applying the values of the spirit of khusyu and khuḍhu’ which illustrates the humility and tepo seliro (tolerance) which are transcendent. Not only on its transcendent and cognitive aspects, but also on the other dimensions of humanity thoroughly and striving in winning nature (fitrah) and logics against lust. [Akhlak merupakan bagian yang sangat penting dalam kehidupan manusia. Tanpa akhlak manusia tidak akan memiliki derajat sebagai manusia mulia, sebaliknya manusia yang berakhlak dapat membedakan antara perbuatan baik dan buruk sehingga menjadi manusia mulia. Persoalan akhlak saat ini mengalami dekadensi akut yang harus cepat diatasi oleh berbagai kalangan. Salah satunya adalah melalui pemikiran ulama-ulama terdahulu. Salah satu ulama yang dimaksud adalah Syaikh Abdul Latief Syakur, salah seorang ulama lokal dari Minangkabau, dimana sisi akademisnya bersentuhan langsung dengan dinamika keilmuan Timur Tengah yang tidak sedikit memberikan warna pemikiran dalam mengangkat harkat martabat bangsa melalui akhlak. Sebagai seorang ulama, Syaikh Abdul Latief Syakur menghadirkan dan menguraikan nilai-nilai akhlak dalam mengatasi dekadensi akhlak masa kini melalui pemikiran yang dituangkan dalam tafsīr surat al- Mukminūn. Penerapan nilai-nilai akhlak dalam tafsir ini memberikan kontribusi kekinian dengan cara menerapkan nilai spirit-spirit khusyu dan khuḍhu’ yang menggambarkan kerendahan hati dan tepo seliro, dimana dari dua unsur tersebut bersifat transenden. Tidak saja yang transenden dan kognitif, tetapi lebih jauh pada dimensi kemanusiaan lainnya secara menyeluruh dan mengupayakan dalam memenangkan fitrah dan akal terhadap hawa nafsu.]